Non-local mind from the perspective of social cognition - Chatel-Goldman, Jonas; Schwartz, Jean-Luc; Jutten, Christian; Congedo, Marco (Frontiers in Human Neuroscience, 2013)
Two main conceptual approaches have been employed to study the mechanisms of social cognition, whether one considers isolated or interacting minds. Using neuro-imaging of subjects in isolation, the former approach has provided knowledge on the neural underpinning of a variety of social processes. However it has been argued that considering one brain alone cannot account for all mechanisms subtending online social interaction. This challenge has been tackled recently by using neuro-imaging of multiple interacting subjects in more ecological settings. The present short review aims at offering a comprehensive view on various advances done in the last decade. We provide a taxonomy of existing research in neuroscience of social interaction, situating them in the frame of general organization principles of social cognition. Finally, we discuss the putative enabling role of emerging non-local social mechanisms – such as interpersonal brain and body coupling – in processes underlying our ability to create a shared world.